Popular music in West Africa - Smith, Edna M. (International Library of African Music, 1962)
The recreational music of the West African people is more subject to change than any other type of music, for it is not ceremonially or socially bound to tribal institutions. Innovations and alterations in this music are not generally prohibited by tradition. Thus it has been changed by outside influences, individuals within the society, and integration with other societies. This music is transient: the forms and styles may persist for a short time and then disappear when new forms are introduced. Konkomba, Adidegbo, and Kolomashie, recreational music that was popular a short time ago, are today only a memory.
Keywords: Ethnomusicology; Highlife (Music); Popular music; Jazz; Africa; West Africa; African Music